Novel frameshift mutations of ANKUB1, GLI3, and TAS2R3 associated with polysyndactyly in a Chinese family. Issue 6 (6th April 2020) - Zhang, Lishan; Chen, Xiaobin; Xu, Lanwei; Guan, Shibing; Wang, Dehua; Lin, Yanliang; Wang, Zengtao
Abstract: Background: Polysyndactyly (PSD) is an autosomal dominant genetic limb malformation caused by mutations. Methods: Whole exome sequencing and Sanger sequencing were used to determine the mutations in PSD patients. Luciferase reporter assay was performed to determine the effect of GLI3 mutation on its transcriptional activity. Results: In this study, we investigated the gene mutations of three affected individuals across three generations. The frameshift mutations of GLI3 (NM_000168:c.4659del, NP_000159.3: p.Ser1553del), ANKUB1 (NM_001144960:c.1385del, NP_001138432.1: p.Pro462del), and TAS2R3 (NM_016943:c.128_131del, NP_058639.1: p.Leu43del) were identified in the three affected individuals, but not in three unaffected members by whole exome sequencing and sanger sequencing. Luciferase reporter assay demonstrated that GLI3 mutation reduced the transcriptional activity of GLI3. The results from SMART analysis showed that the frameshift mutation of TAS2R3 altered most protein sequence, which probably destroyed protein function. Although the frameshift mutation of ANKUB1 did not locate in ankyrin repeat domain and ubiquitin domain, it might influence the interaction between ANKUB1 and other proteins, and further affected the ubiquitinylation. Conclusion: These results indicated that the frameshift mutations of GLI3, ANKUB1, and TAS2R3 might alter the functions of these proteins, and accelerated PSD progression. Abstract : In this study, we investigated the gene mutations of three affected individuals across three generations. The frameshift mutations of GLI3, ANKUB1, and TAS2R3 were identified in the three affected individuals, but not in three unaffected members by whole exome sequencing and Sanger sequencing.